2008
DOI: 10.1002/chem.200800305
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Mechanism of the Transition‐Metal Stereoselective Olefin Cyclopropanation

Abstract: We have carried out a theoretical analysis of the intermolecular cyclopropanation of propargylic esters with alkenes. DFT calculations allow us to propose a reaction mechanism, and provide explanations for the reasons behind the difference between the inter‐ and intramolecular versions of this process. The results strongly suggest that the entropic effects could modulate the operative mechanism and account for the mechanistic discrepancy. The calculated model also justifies the experimental stereoselectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 83 publications
2
34
1
Order By: Relevance
“…The calculated natural population atomic charges at the two carbon atoms are +0.203 e (C a ) and –0.480 e (C b ), which confirms that the positive charge of the complex is centred at C a . These values are consistent with those calculated for a simple unsubstituted propargylic acetate,42b although in our case the positive charge on C a is even higher (+0.203 e vs. +0.063 e), the C a –Au bond length longer (2.73 vs. 2.514 Å), and the C b –Au bond length shorter (2.16 vs. 2.239 Å). On the other hand, alkyne–gold complex V‐Ph has a much more symmetrical structure, with nearly identical Au–C distances (Figure 3), and NPA (natural population analysis) charges (C a = –0.056 e, C b = –0.002 e).…”
Section: Resultssupporting
confidence: 92%
“…The calculated natural population atomic charges at the two carbon atoms are +0.203 e (C a ) and –0.480 e (C b ), which confirms that the positive charge of the complex is centred at C a . These values are consistent with those calculated for a simple unsubstituted propargylic acetate,42b although in our case the positive charge on C a is even higher (+0.203 e vs. +0.063 e), the C a –Au bond length longer (2.73 vs. 2.514 Å), and the C b –Au bond length shorter (2.16 vs. 2.239 Å). On the other hand, alkyne–gold complex V‐Ph has a much more symmetrical structure, with nearly identical Au–C distances (Figure 3), and NPA (natural population analysis) charges (C a = –0.056 e, C b = –0.002 e).…”
Section: Resultssupporting
confidence: 92%
“…For each trajectory, styrene may approach in four different orientations depending on the position of the phenyl group in styrene with respected to the carbonyl group (cis or trans) and the catalyst (endo or exo). 61 Among the four located TSs, only TS11-d adopts the endomode, the others adopt the exo-mode. 3).…”
Section: Achiral Rh 2 (Oac) 4 Modelmentioning
confidence: 99%
“…50 Most previous mechanistic studies employed simplied, achiral catalyst model, such as dirhodium(II) tetraformate Rh 2 (O 2 CH) 4 or dirhodium(II) tetraacetate Rh 2 (OAc) 4 . [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] However, to the best of our knowledge, no theoretical study on the Rh 2 (S-PTTL) 4 -catalyzed cyclopropanation of diazooxindoles has ever been reported. Indeed, recent studies have demonstrated the importance of considering interactions between the Rhcomplex and carbene, as well as the conformational mobility of the ligand in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule of thumb, if substrates I possess electronically unbiased internal alkynes (R 3 ≠H), the 1,3-OXO migration takes place. 13 Alternatively, for tertiary or benzyl alcohol derived substrate I , possessing terminal alkynes (R 3 =H) 14 and electronically biased internal alkynes (R 3 =EWG), 15,16 the 1,2-OXO migration is preferred. However, other factors, such as the choice of metal catalyst, 17 substitution pattern at propargyl moiety, 18 and temperature, 19 in some cases have been reported to govern the regiochemical outcome of these reactions.…”
Section: Introductionmentioning
confidence: 99%